Disiplin Dan Kinerja Pegawai Kesehatan di UPT Puskesmas Muara Laung Tahun 2023 - Rachman, Aulia; Crismilasari, Lucia Andi; Unja, Ermeisi Er (Journal of Nursing Invention, 2023)
Background: Increasing demands for the quality of community services require officers to further improve their performance and professionalism, so that the quality of service is expected to meet community satisfaction. To achieve good performance requires discipline in work which affects services to the community who seek treatment at the community health center Objective: Determine the description of discipline and performance of health employees at UPT Puskesmas Muara Laung Method: The research design used in this study is quantitative descriptive design with observational and survey approach methods. The number of samples used was 30 UPT Muara Laung health centre employees. The research was conducted at UPT Puskesmas Muara Laung. This research has been deemed ethically feasible by the STIKES Suaka Insan Research Ethics Commission with number 031/KEPK-SI/IV/2023. Result: The results showed that the attitude of arriving on time was 20 respondents (66.67%), while those who arrived more than 5 minutes late were 10 respondents (33.33%), and the performance of health employees at UPT Puskesmas Muara Laung in 2023 was good from 30 respondents (100%). So it can be concluded that the description of the implementation of discipline of health centre employees at UPT Puskesmas Muara Laung with the category on time (66.67%), the attitude of responsibility in completing tasks with the category completing on time (100%), the attitude of obedience to office rules using uniforms according to regulations (100%) and making permission letters when absent from work (100%), the description of the performance of health centre employees at UPT Puskesmas Muara Laung with a good category (100%). Conclusion: The implementation of discipline carried out at UPT Puskesmas Muara Laung for employees in the on-time category (66.67%), an attitude of responsibility in completing tasks in the category of completing on time (100%), an attitude of obedience to office rules using uniforms in accordance with regulations (100%) and making permission letters when absent from work (100%), b. Performance of health employees at UPT Puskesmas Muara Laung in the good category (100%).